(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The importance of traditional or alternative medicines including Ayurvedic drugs are increasing day by day because of their necessary pharmacological actions and fewer side effects. Previous investigators showed hypolipidemic and cardioprotective effects of Amla which is the active ingredient of Amalaki Rasayan. It is an ayurvedic formulation that contains extracts of Phyllanthus emblica plant. Therefore, this study has been conducted to investigate the scientific evidence of its cardioprotective effects in rats by recording electrocardiographic tracings. Rats, of either sex, were treated with preparation containing extracts of Phyllanthus emblica in doses 800 μg/kg bodyweight, 1600 μg/kg body weight and 3200 μg/kg body weight through intraperitoneal route. Electrocardiogram along with heart rate and other parameters were measuredin rat model before and after administration of Amalaki Rasayan. It was evident that Amalaki Rasayan, at a dose of 800 μg/kg, was safe but 1600 μg/kg and 3200 μg/kg produced abnormal activities in the heart. It can be inferred from the study that, the ayurvedic preparation Amalaki Rasayan possesses significant cardioprotective effect Bangladesh Pharmaceutical Journal 20(2): 157-164, 2017